PTFE composite material for shaft sleeve and preparation method of PTFE composite material
By adding modified glass fiber and black phosphorene-titanium dioxide-copper nanocomposite to the PTFE composite material of the shaft sleeve, the problem of insufficient performance of existing materials under extreme operating conditions is solved, and higher wear resistance is achieved. Mechanical strength and thermal stability.
Patent Information
- Application Number
- CN202411747539.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-25
AI Technical Summary
The existing PTFE composite shaft sleeves still need to be further optimized under high load, high speed, extreme temperature or corrosive environments to achieve better comprehensive performance.
By using specific filler combination and processing techniques, a PTFE composite material for shaft sleeves is prepared from polytetrafluoroethylene powder, polyphenylene sulfide, modified glass fibers and black phosphorene-titanium dioxide-copper nanocomposites The material is composed of improved wear resistance, mechanical strength and thermal stability.
It significantly improves the wear resistance, mechanical strength and thermal stability of the sleeve material, and meets the wider industrial application needs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a PTFE composite material for a shaft sleeve and a preparation method thereof. Background Art
[0002] In modern industrial applications, as a key mechanical component, the main function of the sleeve is to reduce friction, protect the shaft and bearings, and transmit torque in some cases. With the continuous advancement of industrial technology, the requirements for sleeve materials are also increasing, especially in terms of corrosion resistance, wear resistance, mechanical strength and thermal stability.
[0003] Polytetrafluoroethylene (PTFE) has become one of the preferred materials for bushings due to its unique molecular structure, good chemical stability, extremely low friction coefficient and excellent high and low temperature resistance. However, polytetrafluoroethylene (PTFE) is a thermoplastic polymer, which is polymerized from tetrafluoroethylene (CF2=CF2). Due to the high bond energy of C-F, it has high corrosion resistance. In addition, adjacent fluorine atoms repel each other, causing them to easily slip between PTFE layers, so its wear resistance is poor. This limits its application in certain high-load, high-speed or special environments.
[0004] To overcome these limitations, researchers and engineers have developed a variety of PTFE composite materials. These composite materials usually improve the mechanical properties and wear resistance of PTFE by adding various fillers (such as glass fiber, carbon fiber, graphite, bronze powder, etc.). For example, the addition of glass fiber can increase the bending strength and modulus of PTFE composite materials, while reducing its thermal expansion coefficient, thereby improving the dimensional stability and wear resistance of the sleeve while maintaining a low friction coefficient.
[0005] Although existing PTFE composite bushings perform well in many applications, under some extreme working conditions, such as high load, high speed, extreme temperature or corrosive environment, further optimization of material formulation and processing technology is still needed to achieve better comprehensive performance. Therefore, the present invention aims to provide a new type of PTFE composite bushing, which significantly improves wear resistance, mechanical strength and thermal stability by adopting a specific filler combination and processing technology, so as to meet the needs of a wider range of industrial applications.
[0006] Chinese invention patent CN 118388906 A discloses a surface modified carbon fiber reinforced polyphenyl ester / polytetrafluoroethylene composite material and its preparation method, comprising the following raw materials by weight: 75-80 parts of polytetrafluoroethylene powder, 20-25 parts of modified carbon fiber powder, and 4-6 parts of polyphenyl ester powder. Although the composite material prepared by the invention has good mechanical properties, the wear resistance is poor. While ensuring the mechanical properties, the wear resistance needs to be further improved to expand its application range. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the present invention provides a PTFE composite material for a shaft sleeve and a preparation method thereof.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0009] A PTFE composite material for a shaft sleeve is composed of the following raw materials in parts by weight: 80-140 parts by weight of polytetrafluoroethylene powder, 3-8 parts by weight of polyphenylene sulfide, 8-12 parts by weight of modified glass fiber, and 10-15 parts by weight of a reinforcing agent.
[0010] Pure polytetrafluoroethylene has poor wear resistance and is prone to cold flow, so it is generally not used in dynamic sealing applications. Therefore, various fillers such as bronze powder, glass fiber, carbon fiber, polymers, etc. are often used to fill and modify it to make polytetrafluoroethylene-based composite materials to improve its wear resistance, extrusion resistance and mechanical strength.
[0011] The preparation method of the modified glass fiber is as follows: heat-treating the glass fiber, cooling it to room temperature, adding hydrofluoric acid for etching, washing, and drying to obtain pretreated glass fiber; adding ethanol aqueous solution for ultrasonication, then adding a silane coupling agent for uniform mixing, heating and stirring to obtain modified glass fiber.
[0012] Adding high-strength glass fiber to polytetrafluoroethylene composite materials can improve the interfacial compatibility of glass fiber and polytetrafluoroethylene, so that the composite material has high cyclic tensile strength, flexural strength and flexural modulus, which helps to improve the overall performance of the composite material. At the same time, adding glass fiber can effectively improve the lubrication properties of the substrate. However, directly adding glass fiber is easy to agglomerate in the polytetrafluoroethylene matrix, resulting in poor stability of the composite material. Coupling agent can improve the dispersibility of glass fiber in polytetrafluoroethylene. The inorganic and organic groups in its structure can be combined with fillers and polymers respectively to build a "molecular bridge" to enhance the bonding strength between glass fiber and matrix. It can be used to enhance the overall performance of the composite material, avoid friction damage to the cage or bearing, and effectively improve the stability and reliability of the bearing.
[0013] Preferably, the preparation method of the modified glass fiber is as follows: heat-treating the glass fiber at 320-370°C for 2-4h, cooling to room temperature, taking 5-10 parts by weight of the heat-treated glass fiber, adding 60-140 parts by weight of 7-12wt% hydrofluoric acid, reacting at 35-45°C for 0.5-2h, washing, and drying to obtain pretreated glass fiber; adding 140-260 parts by weight of 40-60wt% ethanol aqueous solution, ultrasonicating for 20-50min at an ultrasonic power of 100-300W and an ultrasonic frequency of 30-60kHz, then adding 0.5-2 parts by weight of a silane coupling agent and mixing evenly, adjusting the pH to 4.5-5.5, stirring at 80-100°C and 400-800rpm for 3-6h, centrifuging, washing, and drying to obtain modified glass fiber.
[0014] The silane coupling agent is fluorine-containing silane.
[0015] As a two-dimensional material, black phosphorene has weak interlayer forces, which makes it easy for layers to slide during friction, thereby reducing the friction coefficient; in addition, a stable lubricating film may be formed during friction, reducing direct contact between friction surfaces and reducing wear. Titanium dioxide nanoparticles have high hardness and chemical stability, which can enhance the surface hardness of polytetrafluoroethylene composites, reduce wear, and play a certain lubricating role during friction. At the same time, its hardness is higher than that of polytetrafluoroethylene, which helps to improve wear resistance. Metal particles can improve the mechanical and tribological properties of polytetrafluoroethylene composites. The good ductility of copper is conducive to the formation of transfer films of polytetrafluoroethylene composites, and the thickness of the transfer film increases slightly with the increase of copper filling. Filling a certain amount of copper can improve the tribological properties of polytetrafluoroethylene composites, reduce the friction coefficient, and extend the service life of the composite. Therefore, the three can improve the tribological properties of composites after being compounded with polytetrafluoroethylene at the same time, including reducing the friction coefficient and improving wear resistance, which is very important for the application of manufacturing anti-friction and wear-resistant parts.
[0016] Titanium dioxide and copper nanoparticles can play a reinforcing role. When the composite material is subjected to external force, these nanoparticles can hinder the expansion of cracks, thereby improving the bending strength and modulus of the material. Black phosphorene, titanium dioxide, and copper nanocomposites may form a strong interface bond with the polytetrafluoroethylene matrix through chemical bonds or physical adsorption, which helps to improve the overall performance of the composite material. Therefore, the addition of black phosphorene-titanium dioxide-copper nanocomposites helps to improve the wear resistance and mechanical properties of polytetrafluoroethylene composites through mechanisms such as improving tribological properties, enhancing mechanical strength, improving interface bonding and load dispersion.
[0017] The preparation method of the enhancer comprises the following steps:
[0018] S1, mixing black phosphorene and isopropanol with ultrasound to obtain a black phosphorene dispersion;
[0019] S2, taking the above-mentioned black phosphorene dispersion, adding isopropyl titanate, copper chloride, sodium borohydride, hexadecyltrimethylammonium bromide and isopropanol, stirring evenly, and then subjecting to hydrothermal reaction; centrifuging, washing, and drying to obtain a composite material primary product;
[0020] S3. In an argon environment, the composite material primary product is placed in a tubular furnace quartz tube for high-temperature calcination to obtain a reinforcing agent.
[0021] Specifically, black phosphorene dispersion, isopropyl titanate, copper salt, and sodium borohydride were used as main raw materials, and a black phosphorene-titanium dioxide-metal nanocomposite material was prepared through a simple hydrothermal reaction and calcination treatment. The preparation method of the present application uses relatively conventional treatment, heating, and calcination methods, has low preparation cost, and is green and environmentally friendly.
[0022] Preferably, the method for preparing the enhancer comprises the following steps:
[0023] S1, mixing 3-8 parts by weight of black phosphorene and 30-80 parts by weight of isopropanol by ultrasonication to obtain a black phosphorene dispersion;
[0024] S2, taking 20-40 parts by weight of the above black phosphorene dispersion, adding 1-3 parts by weight of isopropyl titanate, 0.2-0.5 parts by weight of copper chloride, 0.5-2 parts by weight of sodium borohydride, 3-8 parts by weight of hexadecyltrimethylammonium bromide and 8-20 parts by weight of isopropanol, stirring evenly, and hydrothermally reacting; centrifuging, washing, and drying to obtain a composite material primary product;
[0025] S3. In an argon environment, the composite material primary product is placed in a tubular furnace quartz tube for high-temperature calcination to obtain a reinforcing agent.
[0026] The ultrasonic power in S1 is 600-1000W, the ultrasonic frequency is 80-140kHz, and the ultrasonic time is 0.5-2h.
[0027] The hydrothermal reaction temperature in S2 is 160-200° C., and the hydrothermal reaction time is 8-20 h.
[0028] The calcination temperature in S3 is 450-530° C., and the calcination time is 2-5 hours.
[0029] The preparation method of the PTFE composite material for the shaft sleeve comprises the following steps: mixing polytetrafluoroethylene powder, polyphenylene sulfide, modified glass fiber and a reinforcing agent, stirring evenly to obtain a mixed powder; filling the mixed powder into a mold cavity, placing the mold cavity on a powder tablet press for pressing, the pressing pressure is 40-50MPa, and the pressing time is 5-15min; releasing the pressure, taking out, placing in a high-temperature furnace for sintering, the calcination temperature is 360-400°C, the calcination time is 2-4h, and naturally cooling to room temperature to obtain the PTFE composite material for the shaft sleeve.
[0030] Beneficial effects of the present invention: 1. The present invention provides a PTFE composite material for a shaft sleeve and a preparation method thereof. By adding modified glass fiber to the PTFE composite material of the shaft sleeve, the interface compatibility between the glass fiber and polytetrafluoroethylene is improved, so that the composite material has high annular tensile strength, bending strength and bending modulus.
[0031] 2. Adding black phosphorene-titanium dioxide-metal nanocomposite as a reinforcing agent to PTFE composite materials can not only effectively improve tribological properties, enhance mechanical strength, improve interface bonding and load dispersion, but also help improve the wear resistance and mechanical properties of polytetrafluoroethylene composite materials.
[0032] 3. The preparation method of the present invention is simple, the raw materials are readily available, the cost is low, it is easy to implement, and it is suitable for large-scale industrial production. DETAILED DESCRIPTION
[0033] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.
[0034] Introduction of some raw materials in this application:
[0035] Polytetrafluoroethylene powder was purchased from Dongguan Baojia Plastic Co., Ltd., brand: FR104.
[0036] Polyphenylene sulfide was purchased from Shanghai Chen Yihui Plastic Chemical Co., Ltd. with the brand name PPS R-4-200BL.
[0037] Glass fiber was purchased from Chongqing International Composite Materials Co., Ltd., model: ECS301HP-3-M4.
[0038] Example 1
[0039] The PTFE composite material for the shaft sleeve is composed of the following raw materials in parts by weight: 100 parts by weight of polytetrafluoroethylene powder, 5 parts by weight of polyphenylene sulfide, 10 parts by weight of modified glass fiber, and 12 parts by weight of a reinforcing agent.
[0040] The preparation method of the modified glass fiber is as follows: heat-treating the glass fiber at 350° C. for 3 hours, cooling to room temperature, taking 8 parts by weight of the heat-treated glass fiber, adding 100 parts by weight of 10wt% hydrofluoric acid, reacting at 40° C. for 1 hour, washing, and drying to obtain pretreated glass fiber; adding 200 parts by weight of 50wt% ethanol aqueous solution, ultrasonicating for 30 minutes at an ultrasonic power of 200W and an ultrasonic frequency of 40kHz, and then adding 1 part by weight of perfluorodecyltrimethoxysilane to mix evenly, adjusting the pH to 5, stirring at 90° C. and 600rpm for 4 hours, centrifuging, washing, and drying to obtain modified glass fiber.
[0041] The preparation method of the enhancer comprises the following steps:
[0042] S1, 5 parts by weight of black phosphorene and 50 parts by weight of isopropanol were mixed, and ultrasonically dispersed at an ultrasonic power of 800 W and 100 kHz for 1 h to obtain a black phosphorene dispersion;
[0043] S2, taking 30 parts by weight of the above-mentioned black phosphorene dispersion, adding 2 parts by weight of isopropyl titanate, 0.3 parts by weight of copper chloride, 1 part by weight of sodium borohydride, 5 parts by weight of hexadecyltrimethylammonium bromide and 10 parts by weight of isopropanol, stirring evenly, and then placing in a high-pressure reactor at 180° C. for hydrothermal reaction for 12 hours; centrifuging, washing, and drying to obtain a composite material primary product;
[0044] S3. Under argon environment, place the primary composite material product in a quartz tube of a tubular furnace, heat it to 480°C at a rate of 20°C / min, and calcine it at high temperature for 3 hours to obtain a reinforcing agent.
[0045] The PTFE composite material for a shaft sleeve comprises the following steps: mixing polytetrafluoroethylene powder, polyphenylene sulfide, modified glass fiber and a reinforcing agent, stirring evenly to obtain a mixed powder; filling the mixed powder into a mold cavity, placing the mold cavity on a powder tablet press for pressing, and maintaining the pressure for 10 minutes when the pressure is 45MPa; releasing the pressure, taking out, and placing in a high-temperature furnace for sintering, heating to 320°C at a heating rate of 60°C / h; then heating to 380°C at 40°C / h, and maintaining the temperature for 3h; and naturally cooling to room temperature to obtain the PTFE composite material for a shaft sleeve.
[0046] Example 2
[0047] The PTFE composite material for a shaft sleeve is composed of the following raw materials in parts by weight: 80 parts by weight of polytetrafluoroethylene powder, 3 parts by weight of polyphenylene sulfide, 8 parts by weight of modified glass fiber, and 10 parts by weight of a reinforcing agent.
[0048] The preparation method of the modified glass fiber is as follows: heat-treating the glass fiber at 320° C. for 2 hours, cooling to room temperature, taking 5 parts by weight of the heat-treated glass fiber, adding 60 parts by weight of 7wt% hydrofluoric acid, reacting at 35° C. for 0.5 hours, washing, and drying to obtain pretreated glass fiber; adding 140 parts by weight of 40wt% ethanol aqueous solution, ultrasonicating for 20 minutes at an ultrasonic power of 100W and an ultrasonic frequency of 30kHz, then adding 0.5 parts by weight of perfluorodecyltrimethoxysilane and mixing evenly, adjusting the pH to 4.5, stirring at 80° C. and 400rpm for 3 hours, centrifuging, washing, and drying to obtain modified glass fiber.
[0049] The preparation method of the enhancer comprises the following steps:
[0050] S1, 3 parts by weight of black phosphorene and 30 parts by weight of isopropanol were mixed, and ultrasonic dispersion was performed at an ultrasonic power of 600 W and an ultrasonic power of 80 kHz for 0.5 h to obtain a black phosphorene dispersion;
[0051] S2, taking 20 parts by weight of the above-mentioned black phosphorene dispersion, adding 1 part by weight of isopropyl titanate, 0.2 parts by weight of copper chloride, 0.5 parts by weight of sodium borohydride, 3 parts by weight of hexadecyltrimethylammonium bromide and 8 parts by weight of isopropanol, stirring evenly, and then placing in a high-pressure reactor at 160° C. for hydrothermal reaction for 8 hours; centrifuging, washing, and drying to obtain a primary composite material product;
[0052] S3. Under an argon environment, place the primary composite material product in a quartz tube of a tubular furnace, heat it to 450°C at a rate of 20°C / min, and calcine it at high temperature for 2h to obtain a reinforcing agent.
[0053] The PTFE composite material for a shaft sleeve comprises the following steps: mixing polytetrafluoroethylene powder, polyphenylene sulfide, modified glass fiber and a reinforcing agent, stirring evenly to obtain a mixed powder; filling the mixed powder into a mold cavity, placing the mold cavity on a powder tablet press for pressing, and maintaining the pressure for 5 minutes when the pressure is 40MPa; releasing the pressure, taking out, and placing in a high-temperature furnace for sintering, heating to 320°C at a heating rate of 60°C / h; then heating to 360°C at 40°C / h, and maintaining the temperature for 2 hours; and naturally cooling to room temperature to obtain the PTFE composite material for a shaft sleeve.
[0054] Example 3
[0055] The PTFE composite material for a shaft sleeve is composed of the following raw materials in parts by weight: 140 parts by weight of polytetrafluoroethylene powder, 8 parts by weight of polyphenylene sulfide, 12 parts by weight of modified glass fiber, and 15 parts by weight of a reinforcing agent.
[0056] The preparation method of the modified glass fiber is as follows: heat-treating the glass fiber at 370° C. for 4 hours, cooling to room temperature, taking 10 parts by weight of the heat-treated glass fiber, adding 140 parts by weight of 12wt% hydrofluoric acid, reacting at 45° C. for 2 hours, washing, and drying to obtain pretreated glass fiber; adding 260 parts by weight of 60wt% ethanol aqueous solution, ultrasonicating for 50 minutes at an ultrasonic power of 300W and an ultrasonic frequency of 60kHz, then adding 2 parts by weight of perfluorodecyltrimethoxysilane and mixing evenly, adjusting the pH to 5.5, stirring at 100° C. and 800rpm for 6 hours, centrifuging, washing, and drying to obtain modified glass fiber.
[0057] The preparation method of the enhancer comprises the following steps:
[0058] S1, 8 parts by weight of black phosphorene and 80 parts by weight of isopropanol were mixed, and ultrasonic dispersion was performed at an ultrasonic power of 1000 W and an ultrasonic power of 140 kHz for 2 h to obtain a black phosphorene dispersion;
[0059] S2, taking 40 parts by weight of the above-mentioned black phosphorene dispersion, adding 3 parts by weight of isopropyl titanate, 0.5 parts by weight of copper chloride, 2 parts by weight of sodium borohydride, 8 parts by weight of hexadecyltrimethylammonium bromide and 20 parts by weight of isopropanol, stirring evenly, and then placing in a 200° C. autoclave for hydrothermal reaction for 20 hours; centrifuging, washing, and drying to obtain a composite material primary product;
[0060] S3. Under argon environment, place the primary composite material product in a quartz tube of a tubular furnace, heat it to 530°C at a rate of 20°C / min, and calcine it at high temperature for 5h to obtain a reinforcing agent.
[0061] The PTFE composite material for a shaft sleeve comprises the following steps: mixing polytetrafluoroethylene powder, polyphenylene sulfide, modified glass fiber and a reinforcing agent, stirring evenly to obtain a mixed powder; filling the mixed powder into a mold cavity, placing the mold cavity on a powder tablet press for pressing, and maintaining the pressure for 15 minutes when the pressure is 50MPa; releasing the pressure, taking out, and placing in a high-temperature furnace for sintering, heating to 320°C at a heating rate of 60°C / h; then heating to 400°C at 40°C / h, and maintaining the temperature for 4 hours; and naturally cooling to room temperature to obtain the PTFE composite material for a shaft sleeve.
[0062] Comparative Example 1
[0063] The PTFE composite material for the shaft sleeve is composed of the following raw materials in parts by weight: 100 parts by weight of polytetrafluoroethylene powder, 5 parts by weight of polyphenylene sulfide, 10 parts by weight of glass fiber, and 12 parts by weight of a reinforcing agent.
[0064] The preparation method of the enhancer comprises the following steps:
[0065] S1, 5 parts by weight of black phosphorene and 50 parts by weight of isopropanol were mixed, and ultrasonically dispersed at an ultrasonic power of 800 W and 100 kHz for 1 h to obtain a black phosphorene dispersion;
[0066] S2, taking 30 parts by weight of the above-mentioned black phosphorene dispersion, adding 2 parts by weight of isopropyl titanate, 0.3 parts by weight of copper chloride, 1 part by weight of sodium borohydride, 5 parts by weight of hexadecyltrimethylammonium bromide and 10 parts by weight of isopropanol, stirring evenly, and then placing in a high-pressure reactor at 180° C. for hydrothermal reaction for 12 hours; centrifuging, washing, and drying to obtain a composite material primary product;
[0067] S3. Under argon environment, place the primary composite material product in a quartz tube of a tubular furnace, heat it to 480°C at a rate of 20°C / min, and calcine it at high temperature for 3 hours to obtain a reinforcing agent.
[0068] The PTFE composite material for a shaft sleeve comprises the following steps: mixing polytetrafluoroethylene powder, polyphenylene sulfide, glass fiber and a reinforcing agent, stirring evenly to obtain a mixed powder; filling the mixed powder into a mold cavity, placing the mold cavity on a powder tablet press for pressing, and maintaining the pressure for 10 minutes when the pressure is 45MPa; releasing the pressure, taking out, and placing in a high-temperature furnace for sintering, heating to 320°C at a heating rate of 60°C / h; then heating to 380°C at 40°C / h, and maintaining the temperature for 3h; and naturally cooling to room temperature to obtain the PTFE composite material for a shaft sleeve.
[0069] Comparative Example 2
[0070] The PTFE composite material for the shaft sleeve is composed of the following raw materials in parts by weight: 100 parts by weight of polytetrafluoroethylene powder, 5 parts by weight of polyphenylene sulfide, and 10 parts by weight of modified glass fiber.
[0071] The preparation method of the modified glass fiber is as follows: heat-treating the glass fiber at 350° C. for 3 hours, cooling to room temperature, taking 8 parts by weight of the heat-treated glass fiber, adding 100 parts by weight of 10wt% hydrofluoric acid, reacting at 40° C. for 1 hour, washing, and drying to obtain pretreated glass fiber; adding 200 parts by weight of 50wt% ethanol aqueous solution, ultrasonicating for 30 minutes at an ultrasonic power of 200W and an ultrasonic frequency of 40kHz, and then adding 1 part by weight of perfluorodecyltrimethoxysilane to mix evenly, adjusting the pH to 5, stirring at 90° C. and 600rpm for 4 hours, centrifuging, washing, and drying to obtain modified glass fiber.
[0072] The PTFE composite material for a shaft sleeve comprises the following steps: mixing polytetrafluoroethylene powder, polyphenylene sulfide and modified glass fiber, stirring evenly to obtain a mixed powder; filling the mixed powder into a mold cavity, placing the mold cavity on a powder tablet press for pressing, and maintaining the pressure for 10 minutes when the pressure is 45MPa; releasing the pressure, taking out, and placing in a high-temperature furnace for sintering, heating to 320°C at a heating rate of 60°C / h; then heating to 380°C at 40°C / h, and maintaining the temperature for 3h; and naturally cooling to room temperature to obtain the PTFE composite material for the shaft sleeve.
[0073] Comparative Example 3
[0074] The PTFE composite material for the shaft sleeve is composed of the following raw materials in parts by weight: 100 parts by weight of polytetrafluoroethylene powder, 5 parts by weight of polyphenylene sulfide, 10 parts by weight of modified glass fiber, and 12 parts by weight of a reinforcing agent.
[0075] The preparation method of the modified glass fiber is as follows: heat-treating the glass fiber at 350° C. for 3 hours, cooling to room temperature, taking 8 parts by weight of the heat-treated glass fiber, adding 100 parts by weight of 10wt% hydrofluoric acid, reacting at 40° C. for 1 hour, washing, and drying to obtain pretreated glass fiber; adding 200 parts by weight of 50wt% ethanol aqueous solution, ultrasonicating for 30 minutes at an ultrasonic power of 200W and an ultrasonic frequency of 40kHz, and then adding 1 part by weight of perfluorodecyltrimethoxysilane to mix evenly, adjusting the pH to 5, stirring at 90° C. and 600rpm for 4 hours, centrifuging, washing, and drying to obtain modified glass fiber.
[0076] The preparation method of the enhancer comprises the following steps:
[0077] S1, 5 parts by weight of black phosphorene and 50 parts by weight of isopropanol were mixed, and ultrasonically dispersed at an ultrasonic power of 800 W and 100 kHz for 1 h to obtain a black phosphorene dispersion;
[0078] S2, taking 30 parts by weight of the above-mentioned black phosphorene dispersion, adding 0.3 parts by weight of copper chloride, 1 part by weight of sodium borohydride, 5 parts by weight of hexadecyltrimethylammonium bromide and 10 parts by weight of isopropanol, stirring evenly, and then placing in a high-pressure reactor at 180° C. for hydrothermal reaction for 12 hours; centrifuging, washing, and drying to obtain a composite material primary product;
[0079] S3. Under argon environment, place the primary composite material product in a quartz tube of a tubular furnace, heat it to 480°C at a rate of 20°C / min, and calcine it at high temperature for 3 hours to obtain a reinforcing agent.
[0080] The PTFE composite material for a shaft sleeve comprises the following steps: mixing polytetrafluoroethylene powder, polyphenylene sulfide, modified glass fiber and a reinforcing agent, stirring evenly to obtain a mixed powder; filling the mixed powder into a mold cavity, placing the mold cavity on a powder tablet press for pressing, and maintaining the pressure for 10 minutes when the pressure is 45MPa; releasing the pressure, taking out, and placing in a high-temperature furnace for sintering, heating to 320°C at a heating rate of 60°C / h; then heating to 380°C at 40°C / h, and maintaining the temperature for 3h; and naturally cooling to room temperature to obtain the PTFE composite material for a shaft sleeve.
[0081] Comparative Example 4
[0082] The PTFE composite material for the shaft sleeve is composed of the following raw materials in parts by weight: 100 parts by weight of polytetrafluoroethylene powder, 5 parts by weight of polyphenylene sulfide, 10 parts by weight of modified glass fiber, and 12 parts by weight of a reinforcing agent.
[0083] The preparation method of the modified glass fiber is as follows: heat-treating the glass fiber at 350° C. for 3 hours, cooling to room temperature, taking 8 parts by weight of the heat-treated glass fiber, adding 100 parts by weight of 10wt% hydrofluoric acid, reacting at 40° C. for 1 hour, washing, and drying to obtain pretreated glass fiber; adding 200 parts by weight of 50wt% ethanol aqueous solution, ultrasonicating for 30 minutes at an ultrasonic power of 200W and an ultrasonic frequency of 40kHz, and then adding 1 part by weight of perfluorodecyltrimethoxysilane to mix evenly, adjusting the pH to 5, stirring at 90° C. and 600rpm for 4 hours, centrifuging, washing, and drying to obtain modified glass fiber.
[0084] The preparation method of the enhancer comprises the following steps:
[0085] S1, 5 parts by weight of black phosphorene and 50 parts by weight of isopropanol were mixed, and ultrasonically dispersed at an ultrasonic power of 800 W and 100 kHz for 1 h to obtain a black phosphorene dispersion;
[0086] S2, taking 30 parts by weight of the above-mentioned black phosphorene dispersion, adding 2 parts by weight of isopropyl titanate, 1 part by weight of sodium borohydride, 5 parts by weight of hexadecyltrimethylammonium bromide and 10 parts by weight of isopropanol, stirring evenly, and then placing in a high-pressure reactor at 180° C. for hydrothermal reaction for 12 hours; centrifuging, washing, and drying to obtain a primary composite material product;
[0087] S3. Under argon environment, place the primary composite material product in a quartz tube of a tubular furnace, heat it to 480°C at a rate of 20°C / min, and calcine it at high temperature for 3 hours to obtain a reinforcing agent.
[0088] The PTFE composite material for a shaft sleeve comprises the following steps: mixing polytetrafluoroethylene powder, polyphenylene sulfide, modified glass fiber and a reinforcing agent, stirring evenly to obtain a mixed powder; filling the mixed powder into a mold cavity, placing the mold cavity on a powder tablet press for pressing, and maintaining the pressure for 10 minutes when the pressure is 45MPa; releasing the pressure, taking out, and placing in a high-temperature furnace for sintering, heating to 320°C at a heating rate of 60°C / h; then heating to 380°C at 40°C / h, and maintaining the temperature for 3h; and naturally cooling to room temperature to obtain the PTFE composite material for a shaft sleeve.
[0089] Test Example 1
[0090] Wear performance test: The PTFE composite materials for shaft sleeves prepared in Examples 1-3 and Comparative Examples 1-4 were tested with reference to the national test standard GB / T 3960-2016 “Test methods for sliding friction and wear of plastics”.
[0091] Specifically: the test load is 200N, the wear time is 2h, the rotation speed is 200r / min, the grinding ball uses a 304 stainless steel ball with a diameter of 10mm, the experimental sample size is 30mm×30mm×4mm, and the friction coefficient of the composite material is recorded during the test. Each sample is repeated 6 times, and the average value is taken to analyze the wear amount and calculate the wear rate. The lower the wear rate, the better the wear resistance. The results are shown in Table 1.
[0092] Table 1 Wear performance test results
[0093] Wear rate, % Example 1 0.11 Example 2 0.15 Example 3 0.14 Comparative Example 1 0.29 Comparative Example 2 0.48 Comparative Example 3 0.22 Comparative Example 4 0.20
[0094] Test Example 2
[0095] Mechanical property test: With reference to the national standard GB / T9341-2008 "Test of bending properties of plastics", the bending properties of the PTFE composite materials for shaft sleeves of Example 1 and Comparative Examples 1-4 were tested 5 times for each group, and the average value was taken. The results are shown in Table 2.
[0096] Table 2 Bending performance test results
[0097] Bending strength, MPa Flexural modulus, MPa Example 1 49.5 2013 Comparative Example 1 46.1 1736 Comparative Example 2 35.9 1427 Comparative Example 3 47.3 1868 Comparative Example 4 47.9 1910
[0098] It can be seen from the above results that the PTFE composite material for the shaft sleeve prepared by the present invention has good wear resistance and bending resistance. The reason is that the modified glass fiber is added to the polytetrafluoroethylene composite material, which can improve the interface compatibility of the glass fiber and polytetrafluoroethylene, so that the composite material has high cyclic tensile strength, bending strength and bending modulus, and the addition of glass fiber can effectively improve the lubrication properties of the substrate, the coupling agent can improve the dispersibility of the glass fiber in polytetrafluoroethylene, and the inorganic and organic groups in its structure can be combined with fillers and polymers respectively to build a "molecular bridge" to enhance the bonding strength between the glass fiber and the matrix, which can be used to enhance the overall performance of the composite material, avoid friction damage to the cage or bearing, and effectively improve the stability and reliability of the bearing.
[0099] Black phosphorene can slide easily between layers during the friction process, thereby reducing the friction coefficient; in addition, a stable lubricating film may be formed during the friction process, reducing direct contact between the friction surfaces and reducing wear. Titanium dioxide nanoparticles have high hardness and chemical stability, which can enhance the surface hardness of polytetrafluoroethylene composites, reduce wear, and play a certain lubricating role during the friction process. At the same time, their hardness is also higher than that of polytetrafluoroethylene, which helps to improve wear resistance. Metal particles can improve the mechanical and tribological properties of polytetrafluoroethylene composites. The good ductility of copper is conducive to the formation of transfer films of polytetrafluoroethylene composites, and the thickness of the transfer film increases slightly with the increase of copper filling. Filling a certain amount of copper can improve the tribological properties of polytetrafluoroethylene composites, reduce the friction coefficient, and extend the service life of the composite. Therefore, the three can improve the tribological properties of the composite material after being compounded with polytetrafluoroethylene at the same time, including reducing the friction coefficient and improving the wear resistance, which is very important for the application of manufacturing anti-friction and wear-resistant parts.
[0100] Titanium dioxide and copper nanoparticles can play a reinforcing role. When the composite material is subjected to external force, these nanoparticles can hinder the expansion of cracks, thereby improving the bending strength and modulus of the material. Black phosphorene, titanium dioxide, and copper nanocomposites may form a strong interface bond with the polytetrafluoroethylene matrix through chemical bonds or physical adsorption, which helps to improve the overall performance of the composite material. Therefore, the addition of black phosphorene-titanium dioxide-copper nanocomposites helps to improve the wear resistance and mechanical properties of polytetrafluoroethylene composites through mechanisms such as improving tribological properties, enhancing mechanical strength, improving interface bonding and load dispersion.
Claims
1. A PTFE composite material for a sleeve, characterized in that: The invention is composed of the following raw materials in parts by weight: 80-140 parts by weight of polytetrafluoroethylene powder, 3-8 parts by weight of polyphenylene sulfide, 8-12 parts by weight of modified glass fiber and 10-15 parts by weight of reinforcing agent.
2. The PTFE composite material for a shaft sleeve according to claim 1, characterized in that: The preparation method of the modified glass fiber is as follows: heat-treating the glass fiber, cooling it to room temperature, adding hydrofluoric acid to etch it, washing it, and drying it to obtain a pretreated glass fiber; The ethanol aqueous solution is added for ultrasonic treatment, and then a silane coupling agent is added for uniform mixing, and the mixture is heated and stirred to obtain a modified glass fiber.
3. The PTFE composite material for a shaft sleeve according to claim 2, characterized in that: The silane coupling agent is fluorine-containing silane.
4. The PTFE composite material for a shaft sleeve according to claim 1, characterized in that: The preparation method of the enhancer comprises the following steps: S1, mixing black phosphorene and isopropanol with ultrasound to obtain a black phosphorene dispersion; S2, taking the above-mentioned black phosphorene dispersion, adding isopropyl titanate, copper chloride, sodium borohydride, hexadecyltrimethylammonium bromide and isopropanol, stirring evenly, and then subjecting to hydrothermal reaction; centrifuging, washing, and drying to obtain a composite material primary product; S3. In an argon environment, the composite material primary product is placed in a tubular furnace quartz tube for high-temperature calcination to obtain a reinforcing agent.
5. The PTFE composite material for a shaft sleeve according to claim 4, characterized in that: The ultrasonic power in S1 is 600-1000W, the ultrasonic frequency is 80-140kHz, and the ultrasonic time is 0.5-2h.
6. The PTFE composite material for a shaft sleeve according to claim 4, characterized in that: The hydrothermal reaction temperature in S2 is 160-200° C., and the hydrothermal reaction time is 8-20 h.
7. The PTFE composite material for a shaft sleeve according to claim 4, characterized in that: The calcination temperature in S3 is 450-530° C., and the calcination time is 2-5 hours.
8. The method for preparing the PTFE composite material for a shaft sleeve according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing polytetrafluoroethylene powder, polyphenylene sulfide, modified glass fiber and a reinforcing agent, stirring evenly to obtain a mixed powder; filling the mixed powder into a mold cavity, placing the mold cavity on a powder tablet press for pressing; unloading the pressure, taking out, placing in a high-temperature furnace for sintering, and naturally cooling to room temperature to obtain a PTFE composite material for a shaft sleeve.
9. The method for preparing a PTFE composite material for a shaft sleeve according to claim 8, characterized in that: The pressing pressure is 40-50 MPa, and the pressing time is 5-15 min.
10. The method for preparing a PTFE composite material for a shaft sleeve according to claim 8, characterized in that: The calcination temperature is 360-400° C., and the calcination time is 2-4 hours.
Citation Information
Patent Citations
Surface modified carbon fiber reinforced polybenzoate / polytetrafluoroethylene composite material and preparation method thereof
CN118388906A
Cited By
Friction material capable of reducing Grouan noise as well as preparation method and application of friction material
CN121136332A
Method for improving sintering speed and uniformity of composite shaft sleeve copper powder
CN121315283A